European arbitration: a critical review of the judgment of the Constitutional Court 65/2021, of March 15 - Gómez Jene, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The judgment of the Constitutional Court (CC) granted constitutional protection and annulled a judgment of the High Court of Madrid by virtue of which an arbitral award was annulled. The award, although rendered in equity, arose from a European arbitration, insofar as mandatory EU law was the applicable law to the merits. This circumstance is crucial, since under the CJEU’s Eco Swiss and Achmea judgments, the scrutiny to be exercised by the court hearing the annulment of the award is particularly intense: in the words of the CJEU, the judge must “examine” the application of mandatory EU law. Far from taking into account this case law - applicable to the case - the CC dissociates itself with an interpretation that is difficult to reconcile with the case law of the CJEU. From this perspective, it is worth asking whether the Constitutional Court itself has violated the right of the defendant to due process (art. 24.2 EC), insofar as it has not ruled in accordance with the established system of sources.
Keywords: European arbitration; Mandatory EU law; Statement of reasons; Award in equity; Public policy